Liquid Chromatography-Mass Spectrometry studies on molecular structure of melatonin after Co-60 gamma irradiation - Ahmad-Reza Safdari; Mehran Babri (Open Journal of Chemistry - Peertechz Publications, 2020)
In this work, effects of gamma rays on melatonin as a natural radioprotective agent, have been studied. Selected samples in the form of a) powder and b) solution, were prepared and irradiated by the use of gammacell radiation system under gamma-ray of Co-60 source, at doses from 20 to 2150Gy. The content of irradiated sample vials compared with of the control samples using LC-MS. This revealed many changes, although only in solution samples. Observed changes in the structure of melatonin in aqueous solutions, could be related to the production of free hydrogen and hydroxyl radicals; since both reduction and oxidation products were detected. Any increase in gamma ray doses would cause, proportional decrease in melatonin concentrations as well as increase in reaction products'concentrations. The lack or low impact of gamma rays on solids are related to the low collision crosssection of melatonin for photons, as compared with the water molecules in aqueous solutions.